Gangguan Depresi Selama Pandemi Covid 19 Pada Mahasiswa Keperawatan: Preliminary Study - Jatnika, Galih (JURNAL KESEHATAN KARTIKA, 2025)
Background: Depression is the leading cause of mental disorders in Indonesia. The prevalence of depression, particularly among adolescents, continues to increase, particularly among nursing students, in line with the mental stress caused by the prolonged Covid 19 pandemic. Objective: This preliminary study aims to examine depressive symptoms in nursing students during  Covid 19 pandemic. Method: This study used a descriptive method. A total of 108 nursing students were recruited. The Beck Depression Inventory (BDI) with 21 items was used to assess depressive symptoms. Data collection used Google Forms to assess depressive symptoms. Data analysis used frequency distributions. Results: The study showed that 64.8% of nursing students experienced depressive symptoms during the Covid 19 pandemic. The distribution of depression levels indicated that 20.4% experienced mild depression, 24.0% experienced moderate depression, and 20.4% experienced severe depression. Conclusion: The incidence of depressive symptoms among nursing students has increased in line with the Covid 19 pandemic. Nurses in educational settings are expected to recognize the symptoms of depressive disorders, implement preventive measures, and design nursing interventions for the management of depressive disorders.